The Reflective Entrepreneur - Dimov, Dimo (Routledge Focus on Business and Management, 2017)
In a world where entrepreneurial success often seems deceptively accessible, it is not always clear what makes a person entrepreneurial. In this book, Dimo Dimov offers a reflective insight into the entrepreneurial journey, striking up a conversation about entrepreneurship in order to challenge and untangle existing preconceptions. A discussion of challenges and tensions such as idea versus opportunity, genius versus lunatic, and skill versus luck forms the foundation of the book, while the second part offers actions and considerations which can help the reader to seek opportunities in a fractious environment. The final part of the text focuses on the collective spirit in entrepreneurship, arising from the interplay between participation and outcomes. The author brings a succinct diversity to the field, making this book essential reading for undergraduate and postgraduate students on entrepreneurship courses, as well as scholars, researchers, and practitioners looking for a new perspective on entrepreneurship.